A Comparative Study of Customer Preference and Brand Loyalty Among Leading Two-Wheeler Brands in Kathmandu Valley - Tamang, Tulsi; Gyawali, Achyut (NPRC Journal of Multidisciplinary Research, 2025)
This study aims to investigate the key factors that influences customer preference for two-wheeler brands in the Kathmandu Valley, with a particular focus on leading brands such as Bajaj, Hero, Honda, Yamaha and TVS. A survey using a structured questionnaire was conducted with 117 respondents selected through convenient sampling from various users, showrooms, recondition dealers and workshops. The collected data from this survey were systematically organized, tabulated, analyzed and interpreted to meet the objectives of the study. The analysis revealed several key insights. Men were playing a dominant role in influencing on purchase decisions than women. Ride-sharing had been emerged as the most popular occupation among the surveyed groups which is closely followed by professional roles. Furthermore, both ride-sharing individuals and professional occupations demonstrated a stronger preference for two-wheeler compared to businessmen and other groups. Customer income level significantly impacts buying decision. Price and product quality being the primary determinant factors of the customers’ buying behavior followed by promotional activities. The findings of the research showed that the most popular Motorcycle sold in the market was the Bajaj Pulsar (150cc and 220F models), while in the Scooter category, the Honda Dio led in sales followed by Hero, Yamaha and TVS brands in the Kathmandu Valley. The research concludes that the competing brands that aiming to gain an edge must closely analyze the features and marketing strategies of these dominant models to strengthen their market position and build stronger customer loyalty within this cut throat competitive two-wheeler market of Kathmandu Valley.